Identification of CircRNA–miRNA–mRNA Regulatory Network in Gastrointestinal Stromal Tumor - Zou, Fang-wen; Cao, Ding; Tang, Yi-fang; Shu, Long; Zuo, Zhongkun; Zhang, Lei-yi (Frontiers in Genetics, 2020)
Circular RNA (circRNA) plays an important role in cancer development and progression. However, the role of circRNAs still remains unknown in gastrointestinal stromal tumors (GISTs). In the present study, the differential circRNA expression profile of GISTs was screened by human circRNAs chip and verified by qRT-PCR. circRNA-miRNA interaction and circRNA-miRNA-mRNA network was constructed by Cytoscape, GO and KEGG analyses were performed to assess the function of the mRNA in the network.Totally 543 differentially expressed circRNAs were identified in GISTs, of which 242 were upregulated and 301 were downregulated. Additionally, circRNA-miRNA-mRNA network contained 6 circRNA, 30 miRNA and 308 mRNAs, and the targeted mRNAs were associated with “regulation of biological process”, “intracellular organelle”, “protein binding”, and enriched in Wnt signaling pathway. Furthermore, large-scale clinical validation suggested that hsa_circRNA_061346, hsa_circRNA_103114, hsa_ circRNA_103870 were significantly up-regulated in GISTs and hsa_circRNA_405324, hsa_circRNA_ 406821, hsa_ circRNA_000361 were dramatically down- regulated in GISTs. All of these circRNAs were showed high diagnostic values and most of them were significantly associated with tumor size, mitotic figure, and malignant degrees in GISTs. Our study illuminates that circRNAs were abnormally expressed in GISTs and circRNA-miRNA-mRNA regulatory network is correlated with the pathogenesis of GISTs. Also, the identified six candidate circRNAs might be a critical circRNAs in the occurrence and development of GISTs.